LOGICAL AND RHETORICAL STRUCTURE OF NEWS. CASE STUDY - COTOARĂ, Daniela; MAROUANI, Hanen; TOMI, Paula (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Usually, we read news to form opinions and expand our knowledge. However, especially in the past years, more and more publications are moving apart from being objective. Therefore, we get biased knowledge. In this article, we aim to observe the way information is passed from a logical and rhetorical point of view in different publications. By this, we do not aim to evaluate the morality of the publications or journalists in questions, our aim is purely theoretical (i.e. logical and rhetorical). In order to be able to provide such an analysis, we picked different pieces of news with the same topic from various publications . The chosen topic is irrelevant to the theoretical content, therefore we do not aim to focus on its political or social implications. The decision was made in order to have sufficient material to provide a proper theoretical analysis. It should also be added that any evaluative terms that are going to be used in this article (e.g. ‘biased’, ‘subjective’, ‘not objective’, ‘one-sided’, etc.) are strictly directed to a theoretical perspective, not a moral, social or political one. As already mentioned, our aim is as theoretical as possible: we are interested in the logical and rhetorical structure of a piece of information.